In vitro evaluation of the antiviral activity of heparan sulfate mimetic compounds against Enterovirus 71 - Pourianfar, Hamid Reza; Poh, Chit Laa *; Fecondo, John; Grollo, Lara (Elsevier, 2012)
Enterovirus 71 (EV71) is the causative agent of hand foot and mouth disease (HFMD) and can also cause fatal neurological complications for which currently there is no vaccine or approved antiviral drug. Despite suggestions that heparan sulfate (HS)-like compounds are effective antivirals against various viruses, no research has been undertaken to examine their effects upon EV71. Therefore, this study aimed to investigate the in vitro anti-EV71 effect of HS mimetics (heparin, heparan sulfate, and pentosan polysulfate). The results revealed that all of the compounds exhibited significant antiviral actions (p < 0.05) against EV71 at concentrations less than 250 μg/mL, compared to virus control and positive control, ribavirin. Among the compounds, heparin exhibited the most potent antiviral activity, as 7.81 μg/mL of it prevented the infection by more than 90% (p < 0.05). Assays to reveal the mode of action revealed that all of the compounds were capable of exerting antiviral activity through hindrance of viral attachment to the cells. In addition, some of the compounds could inhibit viral replication when added to cells 1 h before infection, but none significantly reduced viral penetration. Overall, this research revealed that HS mimetic compounds could inhibit EV71 infection, and that HS may be involved in EV71–host cell interactions, as the virus binding to the host cells was significantly hindered by the HS-like compounds but not by ribavirin. Thus, further investigations to discover the molecular mechanisms underlying the anti-EV71 action of HS-like compounds are warranted.